Identifying the best predictive diagnostic criteria for psoriasis in children (< 18 years): a UK multicentre case–control diagnostic accuracy study (DIPSOC study). (1st February 2022) - Burden‐Teh, E.; Murphy, R.; Gran, S.; Nijsten, T.; Hughes, C.; Abdul‐Wahab, A.; Bewley, A.; Burrows, N.; Darne, S.; Gach, J.E.; Katugampola, R.; Jury, C.S.; et al.
Summary: Background: In children, psoriasis can be challenging to diagnose. Difficulties arise from differences in the clinical presentation compared with adults. Objectives: To test the diagnostic accuracy of previously agreed consensus criteria and to develop a shortlist of the best predictive diagnostic criteria for childhood psoriasis. Methods: A case–control diagnostic accuracy study in 12 UK dermatology departments (2017–2019) assessed 18 clinical criteria using blinded trained investigators. Children (< 18 years) with dermatologist‐diagnosed psoriasis (cases, N = 170) or a different scaly inflammatory rash (controls, N = 160) were recruited. The best predictive criteria were identified using backward logistic regression, and internal validation was conducted using bootstrapping. Results: The sensitivity of the consensus‐agreed criteria and consensus scoring algorithm was 84·6%, the specificity was 65·1% and the area under the curve (AUC) was 0·75. The seven diagnostic criteria that performed best were: (i) scale and erythema in the scalp involving the hairline, (ii) scaly erythema inside the external auditory meatus, (iii) persistent well‐demarcated erythematous rash anywhere on the body, (iv) persistent erythema in the umbilicus, (v) scaly erythematous plaques on the extensor surfaces of the elbows and/or knees, (vi) well‐demarcated erythematous rash in the napkin area involving the crural fold and (vii) family history of psoriasis. The sensitivity of the best predictive model was 76·8%, with specificity 72·7% and AUC 0·84. The c ‐statistic optimism‐adjusted shrinkage factor was 0·012. Conclusions: This study provides examination‐ and history‐based data on the clinical features of psoriasis in children and proposes seven diagnostic criteria with good discriminatory ability in secondary‐care patients. External validation is now needed.